Physician Recommendations Trump Patient Preferences in Prostate Cancer Treatment Decisions. (January 2017) - Scherr, Karen A.; Fagerlin, Angela; Hofer, Timothy; Scherer, Laura D.; Holmes-Rovner, Margaret; Williamson, Lillie D.; Kahn, Valerie C.; Montgomery, Jeffrey S.; Greene, Kirsten L.; Zhang, Biqi; Ubel, Peter A.
Objective. To assess the influence of patient preferences and urologist recommendations in treatment decisions for clinically localized prostate cancer.Methods. We enrolled 257 men with clinically localized prostate cancer (prostate-specific antigen <20; Gleason score 6 or 7) seen by urologists (primarily residents and fellows) in 4 Veterans Affairs medical centers. We measured patients' baseline preferences prior to their urology appointments, including initial treatment preference, cancer-related anxiety, and interest in sex. In longitudinal follow-up, we determined which treatment patients received. We used hierarchical logistic regression to determine the factors that predicted treatment received (active treatment v. active surveillance) and urologist recommendations. We also conducted a directed content analysis of recorded clinical encounters to determine if urologists discussed patients' interest in sex.Results. Patients' initial treatment preferences did not predict receipt of active treatment versus surveillance, Δχ 2 (4) = 3.67, P = 0.45. Instead, receipt of active treatment was predicted primarily by urologists' recommendations, Δχ 2 (2) = 32.81, P < 0.001. Urologists' recommendations, in turn, were influenced heavily by medical factors (age and Gleason score) but were unrelated to patient preferences, Δχ 2 (6) = 0, P = 1. Urologists rarely discussed patients' interest in sex (<15% of appointments).Conclusions. Patients' treatment decisions were based largely on urologists' recommendations, which, in turn, were based on medical factors (age and Gleason score) and not on patients' personal views of the relative pros and cons of treatment alternatives.